2018
DOI: 10.1186/s12885-018-4376-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of upper gastrointestinal cancer alarm symptoms in the general population: a nationwide cohort study

Abstract: BackgroundSurvival rates for upper gastrointestinal (GI) cancer are poor since many are diagnosed at advanced stages. Fast track endoscopy has been introduced to prompt diagnosis for patients with alarm symptoms that could be indicative of upper GI cancer. However, these symptoms may represent benign conditions and little is known about the predictive values of alarm symptoms of upper GI cancer in the general population.MethodsThe study is a nationwide cohort study of 60,562 individuals aged 45 years or above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Compared with previous studies on symptom prevalence in the general population, we found that the response rate in our study was comparable or even higher 23,24 . Similar to the findings of this study, we found that the PPVs of gastrointestinal alarm symptoms are low in other DaSC studies 14,15 . Compared with a study on respiratory symptoms in a general population in Britain 25 , we found lower rates of cough and dyspnoea.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared with previous studies on symptom prevalence in the general population, we found that the response rate in our study was comparable or even higher 23,24 . Similar to the findings of this study, we found that the PPVs of gastrointestinal alarm symptoms are low in other DaSC studies 14,15 . Compared with a study on respiratory symptoms in a general population in Britain 25 , we found lower rates of cough and dyspnoea.…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms were selected based on a review of the literature, including national and international guidelines 7,9,17,33 . Other studies derived from DaSC have reported prevalence estimates and predictive values of cancer alarm symptom related to other types of cancer 10,11,[13][14][15] . The respondents were asked whether they had experienced one or more of the specific and nonspecific alarm symptoms: "Have you experienced any of the following sensations, symptoms or discomfort within the past 4 weeks?"…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have already reported predictive values of gynaecological cancer alarm symptoms 13 and upper gastrointestinal cancer. 14 Parts of the methods described below have therefore been previously described. 7 , 12 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…6 7 Most of these guidelines suggest that individuals presenting with symptoms indicative of cancer (alarm symptoms) should be urgently referred to specialised investigative trajectories. Some of the symptoms mentioned in guidelines are commonly occurring and often caused by benign conditions, 8 which poses a clinical challenge due to the rather modest positive predictive values for cancer. On the other hand, most of the cancers must be detected among symptomatic individuals, 4 which justifies the approach with fast-track investigations.…”
Section: Introductionmentioning
confidence: 99%